Analysis of Misconceptions in the Topic of Area and Circumference of a Circle: A Study on Grade 6A Students at SDIT Raudhatul Jannah. - Ulinuha, Widda; Nindiasari, H (Universitas PGRI Sumatera Barat, 2025)
Mathematics plays a crucial role as a foundation for the development of other sciences One of the topics that often triggers misconceptions among elementary school students is geometry, particularly the concept of circles. This study aims to map the forms of student misconceptions related to the concept of circles, identify their causes, and find effective solutions to address them. The research employs a descriptive qualitative approach and was conducted at SDIT Raudhatul Jannah with Grade 6A students as the subjects. Data were collected through written tests, interviews, and observations. The findings reveal that misconceptions about the concept of circles include errors in applying formulas (confusion between area and circumference) and uncertainty in choosing the value of π (22/7 or 3.14). Students tend to memorize formulas without understanding their conceptual meanings, leading to frequent mistakes when solving problems. Moreover, students struggle to differentiate between circumference as the circular boundary length and area as the space within the circle. The lack of visual and concrete teaching aids exacerbates these misconceptions. To address these issues, a learning approach based on visual and manipulative tools is needed, such as using diagrams or circular objects, accompanied by discussions that explain the use of π values in specific contexts. This strategy is expected to help students develop a deeper understanding of the concepts. By employing a real-world contextual approach, student misconceptions can be minimized, thereby enhancing their comprehension of geometry, particularly the concept of circles, in a more holistic manner.